Atrio Ventricular Block And Rheumatoid Arthritis : A Case Report - ZOUZOU , Hanane (Clinical Medicine And Health Research Journal, 2023)
Rheumatoid arthritis is an autoimmune and chronic inflammatory disease, several cardiac complications were reported, including conduction disturbances, we reported a case of complete Atrio-Ventricular block in a patient with rheumatoide artheritis, with obvious extensive calcified Rheumatoid granulomas in the interventricular septum.